2002
DOI: 10.1055/s-2002-26750
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Activity of β-Sitosterol in the Ischaemia/Reperfusion-Damaged Brain of Mongolian Gerbil

Abstract: Aloe vera continues to be used for wound healing as a folk medicine. We previously reported that A. vera gel has angiogenic activity. In this study, we report upon the isolation of an angiogenic component beta-sitosterol from A. vera and examination of its effect upon damaged blood vessels of the Mongolian gerbil. In a chick embryo chorioallantoic membrane assay, beta-sitosterol was found to have an angiogenic effect. It enhanced new vessel formation in gerbil brains damaged by ischaemia/reperfusion, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 16 publications
0
46
0
2
Order By: Relevance
“…This compound was shown to be angiogenic by stimulating neo-vascularization and promoting endothelial cells motility (Choi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This compound was shown to be angiogenic by stimulating neo-vascularization and promoting endothelial cells motility (Choi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants and substances extracted from them have been used for thousands of years, fostering the prevention and treatment of disorders and dysfunctions in humans (Farnsworth et al, 1985;Ortêncio, 1997 (Juárez et al, 2000;Choi et al, 2002;Wang et al, 2004;Melo-Reis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Previous studies have shown that b-sitosterol reduces carcinogen-induced cancer of the colon in rats, 15) and exhibits anti-inflammatory, 16,17) anti-angiogenic 18) and immune-modulating properties. 19,20) Several studies have indicated that b-sitosterol inhibits the growth of various cultured cancer cell lines that are associated with the activation of the sphingmyelin cycle, 21,22) cell cycle arrest 23,24) and the stimulation of apoptotic cell death.…”
mentioning
confidence: 99%